The impact of organizational pressures on environmental performance of firms. (April 2014) - Ramanathan, Ramakrishnan; Poomkaew, Boonchan; Nath, Prithwiraj
<x xml:space="preserve">Abstract</x> The role of various organizational pressures in influencing performance of firms has been an interesting research topic in a variety of fields and has received the attention of researchers working in the field of environmental strategy. Although there are previous studies that have looked at the influence of various pressures in influencing firms' environmental strategies, our study provides a more holistic analysis considering a variety of such pressures in a single framework. We discuss a research study to analyze how pressures from internal and external stakeholders of a firm, economic pressures, environmental regulations, and pressures of environmental compliance have affected environmental performance of firms using data collected from manufacturing firms in the United Kingdom. We have found that internal stakeholders provide the greatest impact in shaping environmental performance of firms, closely followed by economic pressures, environmental regulations, and external stakeholders in that order. Fears of penalties due to environmental compliance have the least impact, although this pressure also has a positive and significant impact on environmental performance.